Nanomaterial-induced mesenchymal stem cell differentiation into osteoblast for counteracting bone resorption in the osteoporotic rats. (December 2021) - Mahmoud, Nadia S.; Mohamed, Mohamed R.; Ali, Mohamed A.M.; Aglan, Hadeer A.; Amr, Khalda S.; Ahmed, Hanaa H.
Highlights: The role of C/HA-NPs and HA-NPs in the differentiation of BM-MSCs into osteoblasts. The significance of osteoblast therapy in mitigating osteoporosis. The promising outcomes of osteoblasts needed to be translated into clinical milieu. Abstract: The current approach was designed to unearth the therapeutic potential of osteoblasts infusion, yielded from cultivating rat mesenchymal stem cells of bone marrow source in osteogenic differentiation media supplied with either hydroxyapatite nanoparticles (HA-NPs), chitosan/hydroxyapatite nanomaterials (C/HA-NPs), or chitosan nanoparticles, in the osteoporotic rats. The successful migration of the osteoblasts to the diseased bones of rats in C/HA-NPs and HA-NPs groups was evidenced by PCR screening of the Y-linked sex-determining gene (SRY) in the femoral bone tissue. Serum bone biomarker levels and gene expression patterns of cathepsin K, receptor activator of nuclear factor kappa B ligand (RANKL), and osteoprotegerin (OPG) were assessed. Additionally, histological examination of the femoral bone tissues of rats was performed. The current outcomes revealed that osteoblast implantation, resulted from C/HA-NPs or HA-NPs group, significantly lessened bone sialoprotein level. In Addition, it yielded a significant decline in the gene expression patterns of cathepsin K, RANKL, and RANKL/OPG proportion as well as up-regulation in BMP-2 and Runx-2 gene expression levels as opposed to the untreated ovariectomized animals. Moreover, it could restrain bone resorption and refine bone histoarchitecture. Conclusively, this study sheds light on the therapeutic significance of osteoblasts transplantation in alleviating the intensity of the bone remodeling cycle, consequently representing a hopeful therapeutic approach for primary osteoporosis.